1960
DOI: 10.1002/bbpc.19600640211
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung des Auf‐ und Abbaues von Wasserstoff‐ und Sauerstoffbelegungen an Platin mit einer neuen instationären Methode

Abstract: Es wird ein Verfahren für elektrodenkinetische Messungen und seine Anwendung zur Untersuchung von Adsorptionserscheinungen an Platin beschrieben. Die Methode besteht im wesentlichen darin, daß zwischen der Versuchselektrode und einer Bezugselektrode praktisch stromlos eine Gleichspannung und cine Dreieckspannung variabler Amplitude und Frequenz mittels eines elektronischen Potentiostaten vorgegeben und der Zellenstrom oszillographisch registriert wird. Steigert man die Frequenz der periodischen Dreieckspannung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1960
1960
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…51 Already in 1960, Will and Knorr reported that the shape of CV voltammograms depends on the crystallographic orientation of the platin-monocrystal electrode. 53 It is attributed to the difference in number of atoms occupying the lattice planes of various Miller indices, thus the binding energy varies. In case of lead UPD at single-crystal gold electrode in perchloric acid, CV voltammogram is composed of up to five peaks on Au (111).…”
Section: Underpotential Deposition Phenomenamentioning
confidence: 99%
“…51 Already in 1960, Will and Knorr reported that the shape of CV voltammograms depends on the crystallographic orientation of the platin-monocrystal electrode. 53 It is attributed to the difference in number of atoms occupying the lattice planes of various Miller indices, thus the binding energy varies. In case of lead UPD at single-crystal gold electrode in perchloric acid, CV voltammogram is composed of up to five peaks on Au (111).…”
Section: Underpotential Deposition Phenomenamentioning
confidence: 99%
“…In the electrochemistry literature of the 1950s and 60s, several investigators reported altered electrochemical activity on platinum depending on the potential range accessed by the electrode. Out of these observations, two theories on the cause of the activity changes arose: (1) scanning through more positive potentials oxidizes contaminants or organic materials in the electrolyte that had adsorbed to the electrode surface, thus freeing surface sites for charge transfer [59][60][61][62] and (2) scanning into the oxide formation potential region elicits 'activation' of the platinum surface, producing a layer of more active platinum sites [63][64][65][66][67]. French and Kuwana estimated that the activated state would revert to the inactivated state with a half-life of 46 minutes [67].…”
Section: Hydrogen Adsorption Is Dependent On the Potential Rangementioning
confidence: 99%